Analisis studi kelayakan terhadap umkm ditinjau dari aspek produksi, sosial-ekonomi, pasar dan pemasaran: Studi pada usaha produksi dan penjualan kelapa di desa Bumirejo, Kabupaten Malang - Khotimah, Siti (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the feasibility of an MSME engaged in coconut production and sales in Bumirejo Village, Malang Regency, from several perspectives using a qualitative approach with a descriptive method. The data used in this study were collected through direct observation, interviews with business owners, and documentation. The results indicate that, from a production perspective, the business operates sustainably and generates added value. Socially and economically, the business serves as a local employer, strengthens household economies, contributes to community income, and stimulates the village-level economy. Regarding market and marketing aspects, the business has strong potential due to stable demand and partnerships with other entities as target markets. Based on the analysis, this business is deemed viable and has potential for development. However, improvements are needed in technology adoption and broader marketing strategies to support the business’s sustainability.